Expression of metabolic and myogenic factors during two competitive seasons in elite junior cyclists - Frese, S.; Valdivieso, P.; Jaecker, V. C.; Harms, S. A.; Konou, T. M.; Tappe, K. A.; Schiffer, T.; Frese, L.; Bloch, W.; Flück, M. (Deutsche Zeitschrift für Sportmedizin, 2016)
We assessed whetherthe seasonal training pattern of endurance athletes produces corresponding adaptations of mitochondrial, angiogenic, and myogenic processes in skeletal muscle and whether these relate to the training volume and metabolic load during exercise. Aerobic performanceand content per actin of markers of mitochondrial respiration (NDUFA9, SDHA, UQCRC1, COX4AI, ATP5A1, UCP3), myogenic regulators (myogenin, myoD, tenascin-C) and MyHC were determined in m. vastus lateralis of ten male elite junior cyclists (17.3±0.2 years) after the preparation and competition phase over two seasons. Effects were assessed with a repeated measures ANOVA at a 5% significance level.' Energy spent in training was comparable in the preparation and competition phase of the first season (9354 and 9825 MET x min/week), despite a 14%-reduced training volume, but decreased thereafter to 6800 MET x min/week. Average mitochondrial protein content changed in anti-cyclical pattern to VO2peak, capillarisation, satellite cell and myonuclear number; being 22% and 45% higher after the preparation than the preceding competition phase in season 1 and 2. The content of tenascin-C (+34%), and myogenin (+166%), increased transiently after the second preparation phase. The findings emphasize a role of seasonal metabolic load for adjustments in muscle protein expression with training of junior cyclists and suggest that the capacity for mitochondrial biogenesis may become exhaustedat the end of the competition phase when muscle enters a regeneration program. Autorreferat